PEMBELAJARAN LIMIT FUNGSI DENGAN TAKSONOMI SOLO UNTUK MENINGKATKAN PEMAHAMAN KONSEPTUAL SISWA - Sri Asih Agustin (CV. Adiba Aisha Amira, 2023)
This article is an exploration on the implementation of limit function mathematics learning and aims to describe learning limit functions with SOLO Taxonomy to improve student’s conceptual understanding. The writing of this article is based on direct observation and interviews of several students. Based on the results of observations made in the environment, there are still many students who find it difficult to solve questions related to the limit function material. This is because the level of understanding or ability each students has towards a different subject matter. The characteristics and understanding of different students in limit function leraning make the writer want to make an innovation in learning with SOLO Taxonomy. Learning limit function material based on SOLO Taxonomy begins by providing a test on the limit function material to determine student level based on SOLO Taxonomy, namely pre-structural, unistructural, multistructual, relational, and extended abstract levels. After determiniting the level of each student and studying it, in learning the content of the limit function material is explained. A questions and answer session was held which then the teacher divided the students into groups. The division of this group is based on different LKPDs according to their level.